Solvent free microwave extraction followed by encapsulation of O. basilicum L. essential oil for insecticide purpose. (March 2020) - Chenni, Mohammed; El Abed, Douniazad; Neggaz, Samir; Rakotomanomana, Njara; Fernandez, Xavier; Chemat, Farid
Abstract: Currently essential oils are increasingly used as natural insecticides because of the adverse effects on human health and environmental pollution of synthetic insecticides. The aim of this study is to perform the encapsulation of Ocimum basilicum L. essential oils by freeze-drying technique using binary mixtures maltodextrins and acacia gum to investigate their insecticidal activity against three insect pests of stored-products Rhyzopertha dominica, Sitophilus oryzae and Tribolium castaneum by direct contact and ingestion toxicity effects. Essential oils were obtained by solvent-free microwave extraction (SFME) and conventional hydro-distillation (HD) methods. Chemical composition of essential oils analysed by GC-MS indicated that the major components were linalool (43.5% for SFME and 48.4% for HD) followed by methyl chavicol (13.3% for SFME and 14.3% for HD) and 1, 8-cineole (6.8% for SFME and 7.3% for HD). The toxic effects results, confirm that O. basilicum essential oils capsules were highly effective against R. dominica than S. oryzae, except for T. castaneum which was insensitive. The toxicity against adults of R. dominica varied between (LD50 = 0.20 g/kg for SFME-EEO, LD50 = 0.25 g/kg for HD-EEO) and (LD50 = 0.32 g/kg for SFME-EEO, LD50 = 0.37 g/kg for HD-EEO) by direct contact and ingestion effect, respectively. These results lead us to consider such essential oils capsules as providing a richer source of natural insecticide agents for food preservation. Graphical abstract: Image 1 Highlights: Essential oils were obtained by solvent-free microwave extraction (SFME) and conventional hydro-distillation (HD) methods. Encapsulation of O . basilicum L. essential oils was performed by freeze-drying technique using binary mixtures maltodextrins and acacia gum. Insecticidal activity was evaluated against three insect pests of stored-products R. dominica, S. oryzae and T. castaneum by direct contact and ingestion toxicity effects. O. basilicum essential oils capsules were highly effective against R. dominica than S. oryzae .